Using the quantum yields of photosystem II and the rate of net photosynthesis to monitor high irradiance and temperature stress in chrysanthemum (Dendranthema grandiflora) - Janka, Eshetu (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.